War room: The people, tactics and technology behind Narendra Modi's 2014 win - NP, Ullekh (New Delhi Lotus Collection, 2019)
War Room stands out as an example of real field work and rigorous research. Anyone who wants to understand how decisions are made in India should read this brilliant study of the BJP.' Dr. Walter K. Andersen author of The Brotherhood in Saffron: The Rashtriya Swayamsevak Sangh and Hindu Revivalism 'Ullekh NP has crafted a well-researched and gripping narrative of how the BJP seized the moment in 2014. Its penetrating analysis of the personalities, politics and methods of Modi and Amit Shah makes it a useful resource for answering the major question of India's near-term political future, Will the BJP in the Modi era realise its ambition of building on 2014 to emerge as the dominant party nationwide?' Sumantra Bose Professor of International and Comparative Politics, London School of Economics, author of Transforming India: Challenges to the World's Largest Democracy 'Ullekh NP tells the story of Narendra Modi's campaign to lead the world's largest democracy. A man ''destined to reign on his own terms'', Modi knew that being resilient was more important than being first and fast. Years after War Room is published, people will refer to it as the book that told the story of India's most spectacular election in May 2014 in all its subtle and magnificent details.' Chitra Subramaniam award-winning journalist and author.
Keywords: Prime Minister; Indian Politics; Narendra Modi